Kualitas Lingkungan pada Tegakan Mangrove di Blok Hutan Mondulambi, Taman Nasional Manupeu Tanah Daru: Environmental Quality in Mangrove Stands in Mondulambi Forest Block, Manupeu Tanah Daru National Park - Endah Wahyuningsih; Clarita Wihelmina Sulastri; Irwan Mahakam Lesmono Aji; Andi Tri Lestari (PERENNIAL, 2024)
Mangrove ecosystems are dynamic and vulnerable to external factors such as temperature, pH, and salinity. Changes in the quality of the environment and external conditions of the mangrove ecosystem can affect the arrangement of vegetation, species diversity, and the health and vulnerability of an ecosystem. The research aims to determine the environmental quality of external factors in the mangrove ecosystem by incorporating supporting data such as biota associations and pollutants. Measurement of environmental quality is carried out on plots of systematically dispersed samples representing ecosystems. The quality of the environment is measured using several parameters, such as temperature, salinity, pH, substrate thickness, and stagnation height, and the data is analyzed using observational and quantitative descriptive methods. The environmental quality conditions of the mangrove ecosystems in the Mondulambi Block, RPTN (National Park Management Resort) Kambatawundut, SPTN (Section of National Park Management) II Lewa, Manupeu Land Daru National Park cover salinity values ranging from 20-30 ‰ (ideal), soil pH ranges from 5-6.5 (tends to be more acidic), water pH ranges from 6-7.5 (optimal), the soil temperature ranged between 25-28°C, the water temperature ranging between 26-29°C (tendered to be lower), the lowest substrate thickness of about 2 cm and the highest thickness of 80 cm, the highest standoff height of about 9 cm, and the lowest standoff heights of around 2 cm. The results of this study describe the conditions of an ecosystem intended to be ideal.